Towards Port-Hamiltonian Modeling of Multi-Carrier Energy Systems: A Case Study for a Coupled Electricity and Gas Distribution System. Issue 2 (2018) - Strehle, Felix; Pfeifer, Martin; Kölsch, Lukas; Degünther, Charlotte; Ruf, Johannes; Andresen, Lisa; Hohmann, Sören
Abstract: Multi-carrier energy systems have been identified as a major concept for future energy supply. For their operation, model-based control methods are necessary whose design requires modular, multi-physical control-oriented models. In literature, there exists no control design model which combines the variables of the networks and system dynamics that go beyond ideal storage elements. Port-Hamiltonian systems represent a promising approach for the scalable modeling and control of multi-carrier energy systems. In this publication we present a case study which illustrates the port-Hamiltonian modeling of an exemplary coupled electricity and gas distribution system. Simulations indicate the plausibility of the presented model.